Towards Intercultural Education: Exploring Perceptions of Cultural Diversity and Identities of Adolescents Living in the Border Area between Spain and Morocco - Beatriz Gallego-Noche; Cristina Goenechea; Miguel Ángel Gómez-Ruiz; Macarena Machín-Alvarez (MDPI AG, 2023)
Borders are complex spaces of relationships and interpretations built from the perspective of cultural diversity. The complexity of these spaces concerns the ways in which they are created, experienced and questioned by the people who inhabit them. They are considered spaces of exclusion but also of educational opportunities. This research aims to explore how adolescents who live at the border area between Spain and Morocco value cultural diversity and different aspects related to the construction of their identities. The cities of Algeciras and La Línea in Spain and Tangier and Tetouan in Morocco were selected, and a questionnaire in Arabic and Spanish was administered to a total sample of 751 adolescents, obtaining a significant sample of the adolescent population (confidence level greater than 95% and estimation error less than 2%). The data were statistically analysed using the SPSS Statistics V24 software programme. The results show significant differences between the Moroccan and Spanish adolescents regarding their perceptions of cultural diversity and how it can be a source of conflict; how they shape their identities and identify with the ways of life and habits of the neighbouring country; and how religion influences their cultural identities.